2021
DOI: 10.3390/biom11040596
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Roughness on Aggregation of Polypeptide Chains: A Monte Carlo Study

Abstract: The self-assembly of amyloidogenic peptides and proteins into fibrillar structures has been intensively studied for several decades, because it seems to be associated with a number of neurodegenerative diseases, such as Alzheimer’s and Parkinson’s disease. Therefore, understanding the molecular mechanisms of this phenomenon is important for identifying an effective therapy for the corresponding diseases. Protein aggregation in living organisms very often takes place on surfaces like membranes and the impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…On the contrary, it appears that the presence of the surface leads to a delay in aggregation. This is in agreement with the Monte Carlo simulations by Co and Li, which revealed that the presence of a weakly adsorbing surface may indeed slow down peptide aggregation [ 24 ]. For this type of surface, the authors also observed that increasing the surface roughness led to a further delay in aggregation.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…On the contrary, it appears that the presence of the surface leads to a delay in aggregation. This is in agreement with the Monte Carlo simulations by Co and Li, which revealed that the presence of a weakly adsorbing surface may indeed slow down peptide aggregation [ 24 ]. For this type of surface, the authors also observed that increasing the surface roughness led to a further delay in aggregation.…”
Section: Discussionsupporting
confidence: 90%
“…This was explained by the rougher surfaces hindering the lateral diffusion of adsorbed peptide monomers along the surface, which prevented them from reaching and attaching to the ends of growing amyloid fibrils. This was recently verified by Co and Li in Monte Carlo simulations [ 24 ]. In this work, we investigate the effect of nanoscale surface topography on the aggregation of human islet amyloid polypeptide (hIAPP) at hydrophilic silicon oxide surfaces.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“… 11 The rate of peptide aggregation on the solid–liquid interface is determined by the affinity (binding force) between the peptide and the solid material and the shape (roughness) of the solid surface. 12 While a high affinity between peptides and solid surfaces enhances their adsorption and inhibits the self-assembly (aggregation) of peptides, solid materials with middle affinities and a rough surface (with a nanoscale morphology) accelerate the aggregation of peptides. In contrast, in a study in which all-atom MD simulations of the conformation of Aβ 16–22 peptides were performed, hydrophobic interactions were found to prevent the formation of β-sheet structures in the presence of gold nanoparticles (NPs).…”
Section: Introductionmentioning
confidence: 99%